The Effect of Problem Based Learning (PBL) Model on Students' Critical Thinking Ability in Class XI Digestive System Concept - Dwi Ratnasari; Maya Rahmawati; Alvi Khaerunnisa; Annisa Fitri Kamilah (International Journal of Biology Education Towards Sustainable Development, 2022)
This study aimed to determine the effect of the problem-based learning model on students' critical thinking skills in the digestive system concept. The samples in this study were taken using a simple random sampling technique with 28 samples, namely 14 students for the experimental class and 14 other students for the control class. The measured variable is students' critical thinking skills, which are obtained from the pretest-posttest results using the Kolmogorov Smirnov normality test, the One Way Anova homogeneity test, and hypothesis testing for learning outcomes using the Independent Sample T-test. The results of the t-test show a significant influence of the problem-based learning model on students' critical thinking skills, with a significance value of 0.001 0.05. This study concludes that the problem-based learning model has an effect on increasing students' critical thinking skills.